Knowledge, Attitude, and Practices towards the COVID-19 Pandemic among Undergraduate Students - Joy Limbong; Kuswinarti Kuswinarti; Truly Deti Rose Sitorus (Althea Medical Journal, 2021)
Background: Coronavirus disease-2019 (COVID-19) has caused serious implications and has received a lot of international attention, especially in public health sector. The main strategy for containing the COVID-19 pandemic includes preventive methods such as wearing masks, which requires individual awareness and initiative to adhere to the protocol. This study described the level of knowledge, attitude, and practices towards the COVID-19 pandemic among undergraduate students who were selected due to their high mobility and rate of activity.Methods: This study used a descriptive design and a cross-sectional approach, conducted from October to November 2020. Undergraduate students from all faculties of Universitas Padjadjaran Year 2017– 2019 were invited to participate, using an online questionnaire to assess the knowledge, attitude, and practices towards the COVID 19 pandemic. The result was given numeric values and scored. The mean value of the scores was used as a reference value to describe the level of knowledge, attitude, and practices.Results: From a total of 483 students, 99.5% had good knowledge, 87.9% had good attitude, and 67% had a good practices towards COVID-19.Conclusions: The overall levels of knowledge, attitudes, and practices towards COVID-19 among undergraduate students are good, as well as the adherence to government health protocols and initiatives in seeking information regarding COVID-19. Several specific areas such as transmission through dead bodies, exercise and vitamin supplementation, and anxiety when reading information about COVID-19 are areas of interest for the improvement of education.